Global Organizations in Muslim World: Origins and Evolution - Ansari, Bashir Ahmad (Politikologija religije, 2022)
After its victory over Greece and the Treaty of Lausanne, the Turkish Republic declared its inability to bear the responsibility for Muslims. For the second time in the history of Islam, the Muslim World found itself without an institution representing them, speaking on their behalf, and defending their causes. This resounding collapse of historic Ottoman Caliphate caused peaceful and violent reactions from time to time, which continues to echo in the horizons of the Muslim World as of today. This paper explores efforts made by the governments of the Muslim majority countries and their peoples through popular and governmental conferences, with the aim of establishing global/ international organizations with legal status that includes representatives of Muslim countries and communities, and work to support Muslim solidarity and unity.